Penerapan Kurikulum At-Turas sebagai Standar Keilmuan Di Ma’had Aly Nurul Jadid - Sitti Maghfiroh Fawaid (Yayasan Literasi Altruis Khatulistiwa, 2025)
The At-Turas curriculum is a learning system based on classical Islamic literature (kitab kuning) rooted in the Islamic intellectual tradition. This study aims to analyze the implementation of the At-Turas Curriculum as a standard of scholarship at Ma’had Aly Nurul Jadid and its implications for the academic quality of the students. The research employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and document analysis. The findings indicate that the implementation of the At-Turas Curriculum at Ma’had Aly Nurul Jadid follows a systematic learning structure, encompassing various Islamic disciplines such as fiqh, tafsir, hadith, ushul fiqh, and tasawwuf. This curriculum is supported by teaching methods such as bandongan, sorogan, bahtsul masail, and mudzakarah, which play a crucial role in enhancing students' understanding of classical texts. Furthermore, the curriculum integrates the pesantren’s traditional methodology with modern academic approaches, fostering a balanced knowledge framework between textual comprehension and contextual understanding. The study concludes that the At-Turas Curriculum significantly contributes to shaping students’ intellectual character, preserving the Islamic scholarly tradition, and addressing contemporary challenges. Therefore, optimizing and developing this curriculum is essential to maintain its relevance in the context of modern Islamic education.